Adoption of Mobile Banking by Microentrepreneurs at the Bottom of the Pyramid - Ruano-Arcos, Leidi; Rodríguez-Orejuela, Augusto; Solís-Molina, Miguel (Cuadernos de Administración, 2020)
The use of mobile phones has increased globally, offering developing countries the opportunity to improve financial inclusion through mobile banking. However, mobile banking has been little adopted by microentrepreneurs at the bottom of the pyramid, and studies that explain this phenomenon is incipient. Therefore, this study aims to establish factors that influence mobile banking adoption by microentrepreneurs, from the Theory of Planned Behavior (TPB), extended to the relative advantage and perceived risk. Using a sample of 101 microentrepreneurs at the bottom of the pyramid, our findings confirmed that attitude, subjective norms, behavior control, and relative advantages positively affect the appropriation of mobile banking. Thus, banks and mobile services providers can focus on these critical factors to increase the mobile banking adoption rate.